PARADIGMA NEW PUBLIC MANAGEMENT (NPM) SEBAGAI KERANGKA REFORMASI BIROKRASI MENUJU KEPEMERINTAHAN YANG BAIK (GOOD GOVERNANCE) DI INDONESIA - Fernanda, Desi (Jurnal Borneo Administrator, 2006)
Recently, good governance constitutes keyword in the framework ofbureaucratic reform, particularly among less-developed countries. The process of achieving good governance, however, is “a long and winding road” indeed. In such a case, NPM might be fruitful in offering strategy, method, principles, and instrument on how to reconstruct and refurbish governmental affairs and practices. The basic idea of NPM is that government must pay more attention to the notion of “public responsiveness”, rather than to the effort of improving “effectiveness over internal management”. In other words, NPM advocates the process of democratizing public administration, as one of the good governance main characteristics. It also means that when government is on-process of being more democratic, the concept of good governance is actually workable. And whenever it works favorably, KKN (Indonesian term of corruption, collution and nepotism) could be significantly reduced.Keywords: kepemerintahan yang baik, new public management, reformasi birokrasi.